AB0052 Polymyalgia rheumatica is characterized by pro-inflammatory, senescent CD8+ T cells. (23rd January 2014) - van der Geest, K.; Abdulahad, W.; Huitema, M.; Kroesen, B.; Rutgers, A.; Brouwer, E.; Boots, A.
Abstract : Background: Polymyalgia rheumatica (PMR) is a frequent, inflammatory rheumatic disease affecting elderly people. Previous studies suggest that T cell mediated immune responses contribute to PMR. However, little is known about CD4+ and CD8+ T cell subsets and their function in PMR. Furthermore, it remains to be elucidated if immune ageing contributes to the development of this ageing-related disease. We hypothesized that senescent T cells can functionally contribute to PMR pathogenesis. Therefore, we studied frequencies of circulating T cell subsets in defined stages of differentiation and assessed functional characteristics of senescent (CD28 null ) T cells in PMR patients. Objectives: The aim of the study is to explore the frequencies and function of distinct T cell subsets in PMR. Methods: Peripheral blood was obtained from eight newly-diagnosed, untreated PMR patients. Thirty-nine healthy age- matched elderly controls were recruited from the Groningen Longevity Cohort. Flow cytometric analysis of CD45RO, CCR7 and CD28 expression was used to enumerate CD4+ and CD8+ T cell differentiation subsets and senescent (CD28 null ) T cells. Furthermore, naïve and memory regulatory T cells were identified based on CD25 and CD45RA expression. In addition, the prevalence of IFN-gamma, TNF, IL-4 and/or IL-17 producing CD4+ and CD8+ T cells was assessed by intracellular cytokine staining of blood samples from all PMR patients and sixteen elderly controls after 4h in vitro stimulation with PMA/calcium-ionophore in the presence of brefeldin A Results: Compared to healthy controls, PMR patients had decreased percentages of circulating terminally differentiated (CD45RO-CCR7-) CD4+ T cells. However, no differences were observed in the percentages of Th1, Th2, or Th17 cells in PMR patients. In addition, percentages of naïve and memory regulatory T cells were normal in PMR patients. In CD8+ T cells of PMR patients, percentages of naïve (CD45RO-CCR7+) cells were decreased. Interestingly, percentages of CD28 null cells were increased within the effector memory (CD45RO+CCR7+) and terminally differentiated CD8+ T cell populations of PMR patients. Moreover, a significantly increased potential to produce IFN-gamma and TNF was observed in CD8+T cells of PMR patients. Conclusions: Our data show premature immune ageing (loss of CD28) of effector memory and terminally differentiated CD8+T cells in PMR patients. This is associated with an enhanced pro-inflammatory potential of CD8+ T cells. In contrast, Th subsets and regulatory T cells are not altered in PMR patients. Together, these findings imply a role for pro-inflammatory, senescent CD8+ T cells in PMR pathogenesis. Disclosure of Interest: None Declared